2014
DOI: 10.1021/jf500968b
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Compounds Extracted from Cortex Pseudolaricis against Colletotrichum gloeosporioides

Abstract: Cortex Pseudolaricis is the root bark of Pseudolarix amabilis Rehder, found only in China, and has been widely used in folk antifungal remedies in traditional Chinese medicine. In order to find the natural antifungal agents against mango anthracnose, eight compounds, namely pseudolaric acid A (1), ethyl pseudolaric acid B (2), pseudolaric acid B (3), pseudolaric acid B-O-β-d-glucoside (4), piperonylic acid (5), propionic acid (6), 3-hydroxy-4-methoxybenzoic acid (7), and 4-(3-formyl-5-methoxyphenyl) butanoic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 26 publications
1
34
0
Order By: Relevance
“…The morphological changes induced by PAB in C. gloeosporioides are similar to those caused by microtubule inhibitors. 28 Recent studies have suggested that the antitumor activity of PAB could be associated with its ability to inhibit cell proliferation and induce cell apoptosis related to microtubule depolymerization. 29 Microtubules, composed of α - and β-tubulin heterodimers, are responsible for a variety of biological functions including sustained shapes, the intracellular transport and the cell division.…”
Section: Discussionmentioning
confidence: 99%
“…The morphological changes induced by PAB in C. gloeosporioides are similar to those caused by microtubule inhibitors. 28 Recent studies have suggested that the antitumor activity of PAB could be associated with its ability to inhibit cell proliferation and induce cell apoptosis related to microtubule depolymerization. 29 Microtubules, composed of α - and β-tubulin heterodimers, are responsible for a variety of biological functions including sustained shapes, the intracellular transport and the cell division.…”
Section: Discussionmentioning
confidence: 99%
“…Natural plant chemicals, which are the major sources of industrial and medicinal materials, including plant extracts and essential oils, have also shown potential for agricultural pest management [ 28 , 29 ]. For example, Vitex agnus-castus extract exhibited strong antifungal activity against Pythium ultimum in tomatoes under both in vitro and in vivo conditions [ 30 ]; Cortex Pseudolaricis extract exhibited potential antifungal activity against Colletotrichum gloeosporioides [ 31 ]; and the essential oil from Tetradium glabrifolium fruits showed larvicidal activity against Aedes albopictus [ 32 ]. In addition, glucosinolates, terpenoids, flavor compounds, and glucosinolates are receiving increased attention worldwide [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The protective activity of cuminic acid against F. oxysporum or C. lagenarium was conducted as follows [ 30 ]. One cucumber plant per pot, at a similar growth stage (three to five leaves), were irrigated with 10 mL of water, and carbendazim at 500 μg/mL or cuminic acid at 500, 1000 or 2000 μg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…The inhibitory activity of α-mangostin against the mycelial growth of twenty plant pathogenic fungi was tested according to Zhang et al [ 37 ]. Potato dextrose agar (PDA) was used as the basal medium for all tested fungi except for Phytophthora capsici , which was tested in lima bean agar medium.…”
Section: Methodsmentioning
confidence: 99%